Internal Kurdish Coherence Analyzing Alliances, Capacities, Threats, and Political Objectives of Kurdish Groups and Parties in Syria and Iraq 2015-2017 - Vestenskov, David (Scandinavian Military Studies, 2019)
The Islamic State in Iraq and Syria (ISIS) shocked the world when it entered the world stage in 2014. By seizing large territories in Syria and Iraq, its expansion within the Middle East seemed unrestrainable as the Iraqi Army fell apart and in Syria, various actors were caught up in a bloody civil war in the wake of the Arab spring. With US support, the Syrian and Iraqi Kurds became the main stand against ISIS acting as boots on the ground. The Kurdish success against ISIS in both Syria and Iraq quickly won them acclaim from the West and rendered them the key ally in the continued US-led effort against ISIS. In Western media and among Western decision makers, the Kurds as an entity are highly praised for their role in this fight. In addition, their fight for human rights, gender equality, secular rule, and democracy has also been highlighted as key features in assessing Kurds as a homogeneous entity that almost naturally shares strategic interest with the West. This book, as it sets out to paint a more comprehensive picture of the different Kurdish groups in Syria and Iraq, concludes that these groups indeed have very different policy objectives and diverging regional partners of alliance thereby questioning the underlying assumption of a uniformed Kurdish entity. The book makes a significant contribution to a better understanding of the political goals, affiliations and rivalries of these important actors and Western allies in the Middle East.